Graphene oxide as a novel tool for mycotoxin removal. (March 2021) - Bytesnikova, Zuzana; Adam, Vojtech; Richtera, Lukas
Abstract: Mycotoxins, as a food and feed toxins, pose serious health risks for humans and animals and cause huge economic losses. Preventive measures against mycotoxins are not successful, and mycotoxins are commonly present in food and feed, which are easily contaminated. Moreover, this represents entry into the food chain, endangering all, including humans. Graphene oxide (GO) and its composites, thanks to their number of different functional groups on their surface, seem to be a promising tool for capturing and removing mycotoxins from contaminated food and feed without creating health risks or decreasing the quality of products. Highlights: Graphene oxide and the composite of graphene oxide with magnetic NPs can adsorb mycotoxins from various food and feed. The comparison of traditional methods for mycotoxins removal with nanomaterials. The interactions between nanomaterial and mycotoxins is similar like for antibiotics. PH values play the most important role in the adsorption of mycotoxins.